Assessment of Maintenance Management Practice in Government-owned Tertiary Institution - Osuya, Lucky Azubike; Adenuga, Olumide Afolarin; Oshodi, Olalekan Shamsideen (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2023)
The state of utilities and infrastructure within an academic institution plays a vital role in learning and the development of human capital. Hence, this study seeks to examine the management practices used in maintaining facilities in a government-owned tertiary institution and then examine the conditions of critical facilities and their related services in the institution. To achieve the study's goal, a questionnaire survey approach was used to collect information about users' and property managers' perceptions of maintenance management practices. The results revealed the existence of a maintenance policy covering critical systems and services. The discovery also implies that maintenance tasks are generated and planned in response to inspections and user requests. Respondents' perceptions of the state of facilities and utilities indicate that they are in good condition. While literature shows school infrastructure issues remain an ongoing concern, the majority of respondents affirm security and electricity as the most important critical infrastructure and services in the institution, amongst others. The most important limitation of the current study lies in the fact that the findings may not be generalizable to other tertiary institutions in Nigeria. Hence, more research needs to be done in order to gather more information about maintenance management practices in public universities and other educational institutions to improve critical facilities and services to enhance learning outcomes.